Researches on new and simple test for elifferentiation of tuberculosis anel brucellosis - Veysi ASLAN (Eurasian Journal of Veterinary Sciences)
This research was carried out on a total of 50 ili animals suspected from tuberculosis and brucellosis which were brought to the clinics of Veterinary Faculty and on 10 healthy cattle that have being raised at o ur experimental farm. All of the animals were inspected clinically and the new and simple test ,Balcı test was applied to those ones with tuberculosis and brusellosis. Based on the test evaluation, tuberculin was given in the case positive reaction and the serological methods were applied in the brusellosis incidents. The Balcı and tuberculin tests were both positive at 25 samples out of 40, the Balcı test was positive, but the tuberculin test was negative for 5 samples; on the other hand the Balcı and tuberculin were both negative for 10 samples. The same test was applied to 8 cattle and 2 rams with bruceilasis and a positive relation was obtained. This was affirmed by the Iabaratarial findings. Methodology of Balcı test : A. Solutions 1 - 0.75 % Eosin Solution (Solution A). This solution was obtained by dissolving Eosin in distilled water. 2 - Glycine - saline Buffer solution (pH 8.2), obtained by dissolving 7.5 gr glycine in 977 cc distilled water adding 2.5 cc 1 N Na OH the mixture was levelled to 1000 cc by adding distilled water and furthermore 8.5 gr NaCL was added. 3 - 1 % CaCL2 solution, obtained by dissolving 1 gr granul ated pure CaCI2 in 100 cc distiled water. 4 - Three parts of Glycine - Saline Buffer Solution were mixed with one part of 1% CaCI2 solution. Sodium Acide of 1/20 concentration in distiled water was added to this mixture until the mixture reached a sodium acide concentration of 1/2000. The resulting mixture was used in the test and it is called solution B. B. Aplication A full drop of blood obtained from the top of ear was placed on a slide. A drop of solution was added and mixed with the tip of the lanset and the mixture was spread over the slide. Next a drop of solution B was added, mixed and spread smilarly. The slide was rolled back and forth a couple of times. When many red granulations appeared in the mixture within two minutes the test was considered as positive.